2020
DOI: 10.3390/cells9040981
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Phospholipids in Healthy and Diseased Lung Endothelium

Abstract: Circulating and cell membrane phospholipids undergo oxidation caused by enzymatic and non-enzymatic mechanisms. As a result, a diverse group of bioactive oxidized phospholipids generated in these conditions have both beneficial and harmful effects on the human body. Increased production of oxidized phospholipid products with deleterious effects is linked to the pathogenesis of various cardiopulmonary disorders such as atherosclerosis, thrombosis, acute lung injury (ALI), and inflammation. It has been determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 143 publications
1
25
0
Order By: Relevance
“…Phospholipids are the building blocks of all mammalian membranes, ensuring a permeable barrier and endogenous substrates in multiple enzymatic pathways usually involved in the formation of essential signaling mediators (eg, platelet‐activating factor, sphingosine‐derived phospholipids, and eicosanoids) 47 . However, several pathological conditions, including lung injury, autoimmune diseases, and sepsis, promote oxidative stress with the consequent formation of fatty acid hydroperoxides and further accumulation of full‐length and fragmented OxPLs in cell membranes and circulating lipoproteins 48 . OxPLs elicit a multiplicity of bioactivities by interacting with different pattern recognition receptors of the innate immune system cellular receptors, including TLRs and scavenger receptors 48,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phospholipids are the building blocks of all mammalian membranes, ensuring a permeable barrier and endogenous substrates in multiple enzymatic pathways usually involved in the formation of essential signaling mediators (eg, platelet‐activating factor, sphingosine‐derived phospholipids, and eicosanoids) 47 . However, several pathological conditions, including lung injury, autoimmune diseases, and sepsis, promote oxidative stress with the consequent formation of fatty acid hydroperoxides and further accumulation of full‐length and fragmented OxPLs in cell membranes and circulating lipoproteins 48 . OxPLs elicit a multiplicity of bioactivities by interacting with different pattern recognition receptors of the innate immune system cellular receptors, including TLRs and scavenger receptors 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…However, several pathological conditions, including lung injury, autoimmune diseases, and sepsis, promote oxidative stress with the consequent formation of fatty acid hydroperoxides and further accumulation of full‐length and fragmented OxPLs in cell membranes and circulating lipoproteins 48 . OxPLs elicit a multiplicity of bioactivities by interacting with different pattern recognition receptors of the innate immune system cellular receptors, including TLRs and scavenger receptors 48,49 . In contrast to these pro‐inflammatory effects, OxPLs have also been shown to mediate anti‐inflammatory responses by negatively influencing the activation of TLRs following exposure to microbial ligands 11,33,50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…The full-length oxPLs exert anti-inflammatory effects and are protective for inflammatory diseases while truncated oxPLs exhibit pro-inflammatory activity and promote the development and progress of inflammatory diseases [ 54 ]. Therefore, the biological impacts upon the exposure to mixture of oxPLs in vivo could be different depending on the composition and concentration of oxPL components and the cellular context [ 54 ]. Ray et al evaluated the free radical production and malondialdehyde (MDA) concentration in the plasma of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies confirmed the protective effects of polyphenol and flavonoids' antioxidants against many pathological pathologies including neurodegenerative [107], vascular [108], and cardiovascular diseases [109]. Furthermore, numerous scientific investigations have highlighted the protective role of polyphenols against endothelial and microvascular dysfunctions [110,111].…”
Section: Therapeutic Interventions In Endothelial Dysfunction and In mentioning
confidence: 92%